2023
DOI: 10.20944/preprints202302.0097.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep Learning-Based Prediction of Diabetic Retinopathy Using CLAHE and ESRGAN for Enhancement

Abstract: Vision loss can be avoided if diabetic retinopathy (DR) is diagnosed and treated promptly. Following are the main 5 DR stages: none, moderate,  mild, proliferate, and severe. In this study, a deep learning (DL) model is presented that diagnoses all 5 stages of DR with more accuracy than previous methods. The suggested method presents two scenarios: case 1 with image enhancement using contrast limited adaptive histogram equalization (CLAHE) filtering algorithm in conjunction with an Enhanced Super-resolution ge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…An enhancement upon traditional AHE methods, contrast limited adaptive histogram equalization (CLAHE) was introduced by clipping histograms to constrain the contrast (16). Recently, several studies have shown the advantages of CLAHE on DL-related tasks, such as predicting five stages of diabetic retinopathy (17), segmenting temporomandibular joint articular disks from magnetic resonance images (18), and classification of COVID-19 and other pneumonia cases (19).…”
Section: Introductionmentioning
confidence: 99%
“…An enhancement upon traditional AHE methods, contrast limited adaptive histogram equalization (CLAHE) was introduced by clipping histograms to constrain the contrast (16). Recently, several studies have shown the advantages of CLAHE on DL-related tasks, such as predicting five stages of diabetic retinopathy (17), segmenting temporomandibular joint articular disks from magnetic resonance images (18), and classification of COVID-19 and other pneumonia cases (19).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic retinopathy (DR) is a devastating condition that can lead to blindness in advanced stages. 6 8 The majority of diabetes patients suffer from non-proliferative retinopathy (NPD). In the beginning stages of the disease, the central retina has edema and hard exudates, which are lipids that possibly leaked from abnormal blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 Nevertheless, with prophylactic therapy and severe surveillance, roughly 56% of new DR cases can be reduced. 4 , 5 Microaneurysms, hard/soft exudates, and hemorrhages are examples of lesion-based symptoms that the ophthalmologist looks for in retinal pictures to determine the severity stages of DR. 6 , 7 There are several levels to a DR in a good direction 5 , 8 : There are four stages of atherosclerosis: (i) mild, in which microaneurysms can still be contained; (ii) moderate, wherein veins lose their ability to carry blood; (iii) severe, when blood channel blockages form and alert the body to produce new blood cells; and (iv) proliferative, wherein new arteries start sprouting. Some fundus pictures illustrating the different DR severity levels are depicted in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%